2022
DOI: 10.1136/bmjdrc-2021-002704
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes epidemic and key risk factors in Qatar: a mathematical modeling analysis

Abstract: IntroductionWe aimed to characterize and forecast type 2 diabetes mellitus (T2DM) disease burden between 2021 and 2050 in Qatar where 89% of the population comprises expatriates from over 150 countries.Research design and methodsAn age-structured mathematical model was used to forecast T2DM burden and the impact of key risk factors (obesity, smoking, and physical inactivity). The model was parametrized using data from T2DM natural history studies, Qatar’s 2012 STEPwise survey, the Global Health Observatory, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…About 60% of Qatar’s population are craft and manual workers (CMW) 13,14 who are typically single men, 20-49 years of age. 25 CMW are healthy by recruitment (healthy worker effect 26,27 ) and have lower levels of comorbidities such as diabetes and obesity; 28 that is a population not likely to be affected by the pull forward effect.…”
Section: Discussionmentioning
confidence: 99%
“…About 60% of Qatar’s population are craft and manual workers (CMW) 13,14 who are typically single men, 20-49 years of age. 25 CMW are healthy by recruitment (healthy worker effect 26,27 ) and have lower levels of comorbidities such as diabetes and obesity; 28 that is a population not likely to be affected by the pull forward effect.…”
Section: Discussionmentioning
confidence: 99%
“…CMWs may also have lower levels of comorbidities, such as diabetes and obesity. 31 Meanwhile, Qataris are a typical national population that includes both healthy and unhealthy individuals. Studies also suggest high prevalence of specific comorbidities or risk factors among Qataris, such as diabetes, obesity, hypertension and physical inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also suggest high prevalence of specific comorbidities or risk factors among Qataris, such as diabetes, obesity, hypertension and physical inactivity. 31–36 Deaths due to road injuries may affect Qataris and the urban population more than CMWs. CMWs are unlikely to own cars, but use buses for transportation, unlike Qataris and the urban population who have high socioeconomic status and car ownership ratios.…”
Section: Discussionmentioning
confidence: 99%
“…While there are studies that have established the prevalence of T2D in the Middle East and Africa, [21][22][23][24][25][26] there is limited information on the prevalence of eASCVD or on high/very high ASCVD risk in patients with T2D in this region. 3,[27][28][29][30][31] The CAPTURE study estimated the prevalence of ASCVD among patients with T2D across 13 countries from five continents and showed that one in three adults with T2D have established CVD, of which 9/10 had ASCVD.…”
Section: Discussionmentioning
confidence: 99%